Reclaiming Narratives: Indigenous Sovereignty in Art and Media (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research delves into the depiction of communities in artistic expressions and media, shedding light on the historical inaccuracies and the endeavors of Native American artists to reclaim and redefine their stories. It documents the transition from portrayals to modern artworks, encapsulating their cultural heritage and resilience. By conducting an analysis, this study uncovers the effects of misrepresentation and cultural appropriation on Native American societies. Additionally, it showcases how Native American artists leverage art for preserving their culture advocating resistance and engaging in dialogues. The investigation is grounded in research and a detailed exploration of significant artworks that perpetuate stereotypes alongside initiatives aimed at reclaiming Native American narratives. At its core this research tackles the issue of misrepresenting communities in art and media which not only marginalizes these groups but also distorts their rich cultural heritage. It posits that achieving a respectful portrayal necessitates acknowledging these inaccuracies while amplifying the authentic voices and perspectives of Native American artists. Furthermore, it calls for art institutions and society at large to embrace approaches that amplify voices while recognizing art’s transformative power in driving societal change. The paper advocates for supporting artists in reclaiming their identities.The paper highlights the significance of acknowledging the arts' capacity to drive transformation by advocating for the appreciation and comprehension of viewpoints in art and media, thereby fostering a more diverse and fairer cultural environment.